Evaluation of potential pharmacodynamic and pharmacokinetic interactions between verapamil and propranolol in normal subjects. - Murdoch, D L (1991)
1. Potential pharmacodynamic and pharmacokinetic interactions between verapamil and propranolol were evaluated in two double-blind, randomised, balanced, crossover studies employing the same six healthy males. 2. The first study examined the effect of repeated propranolol administration on the pharmacodynamics and pharmacokinetics of verapamil after single oral and intravenous doses. The second explored the pharmacodynamics and pharmacokinetics of verapamil and propranolol alone and in combination after single and repeated oral doses. 3. The magnitude of the prolongation of PR interval induced by oral and intravenous verapamil was not affected by pre-treatment with propranolol. When verapamil and propranolol were co-administered as single doses, effects on PR interval were additive but, following repeated doses, a trend towards greater than additive prolongation was seen. The arithmetic sum of the effects of the two drugs was 23% (95% C.I. 8-38%) but the measured increase after the combination was 40% (95% C.I. 26-54%). 4. The extent of reduction in heart rate and blood pressure at rest and after exercise following repeated doses of propranolol was not influenced by single oral or intravenous doses of verapamil. The heart rate and blood pressure responses to single and repeated oral doses of verapamil and propranolol in combination were significantly greater than those after either drug alone and approximated to the arithmetic sum of the individual responses. 5. Although repeated administration of propranolol reduced hepatic blood flow as assessed by indocyanine green clearance, there was no evidence of an interaction between the drugs at this level. 6. The pharmacokinetics of verapamil and norverapamil were not significantly affected by prior propranolol. After single doses of verapamil and propranolol in combination, the maximum plasma concentration of propranolol was increased and the oral clearance of verapamil reduced. No pharmacokinetic interaction was observed after repeated doses. 7. These findings provide little evidence of a pharmacodynamic or pharmacokinetic interaction between verapamil and propranolol in normal subjects. Most of the haemodynamic responses to these drugs in combination can be explained by additive drug effects but an interaction affecting AV conduction after repeated doses cannot be excluded. The minor pharmacokinetic interaction between the drugs is unlikely to be relevant to the pharmacodynamic changes.